Literature study of the Nyabuk Gunung tradition in the communities on the slopes of Mount Sumbing as an effort to conserve agricultural land - Nabila, Revani Ayu; Surtikanti, Hertien Koosbandiah (Institute for Advanced Science, Social, and Sustainable Future, 2024)
Background: Central Java has a variety of cultures and customs that are unique and interesting to learn. One is a farming system with uneven and sloping land for people living around the mountains. This article describes a farming system in Central Java society called Nyabuk Gunung, namely how to grow crops by making rice terraces formed according to contour lines. Method: The research method used in this research is qualitative descriptive, with data collection techniques of literature studies, field observations, and farmer interviews. A literature study is a method used to collect data or sources related to the topics raised in a study. Findings: The results of this study indicate that the surrounding community created the Nyabuk Gunung farming system in addition to utilizing existing land to prevent erosion and landslides on their land. Conclusion: Plants planted by the community in suitable plantation crops are located in the highlands, such as tea, coffee and other vegetable crops. Novelty/Originality of this article: The Nyabuk Gunung farming system can be a solution for agriculture in the Central Java region, which has mountainous topography as land conversion and prevents natural disasters such as landslides.